Evidence relating to Object-Oriented software design: A survey - G V S Ch S L V Prasad,M.Rambabu,Dr.Y V R Naga Pawan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Context: There is little empirical knowledge of the effec- tiveness of the object-oriented paradigm. Objectives: To conduct a systematic review of the literature describing empirical studies of this paradigm. Method: We undertook a Mapping Study of the literature. Results: 138 papers have been identiﬁed and classiﬁed by topic, form of study involved, and source. Conclusions: The majority of empirical studies of OO con- centrate on metrics, relatively few consider effectiveness